35. EVALUATION OF THE THERAPEUTIC EFFECTS OF THE “KIEN THONG THANG 103” COMBINED WITH ELECTROACUPUNCTURE AND HYDROACUPUNCTURE IN PATIENTS WITH CERVICAL SHOULDER ARM SYNDROME DUE TO CERVICAL SPONDYLOSIS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the therapeutic effects of the “Kien thong thang 103” combined withelectroacupuncture and hydroacupuncture in patients with cervical shoulder arm syndrome due tocervical spondylosis.Methods: This is a prospective study, pre- and post-treatment comparison with control on 60 patientsdiagnosed with cervical shoulder arm syndrome due to cervical spondylosis. The patients weretreated at the Department of Traditional Medicine, Military Hospital 103 from January 2024 toDecember 2024.Results: After 15 days of treatment, the study group showed significant improvements in VAS scores,cervical spine range of motion, and NDI scores compared to pre-treatment values (p < 0.05). Thedegree of improvement in these indicators was greater and statistically significant compared to thecontrol group (p < 0.05).Conclusion: The “Kien thong thang 103” combined with electroacupuncture and hydroacupuncturedemonstrated good therapeutic efficacy in patients with cervical shoulder arm syndrome due tocervical spondylosis.
Keywords: Cervical shoulder arm syndrome, cervical spondylosis, electroacupuncture, hydroacupuncture, Kien thong thang 103.